Relations between professional ethic and labour performance in teachers of a district of the Cono Norte of Lima - Torres Valladares, Manuel (2011)
The fundamental purpose of the current investigation work was to obtain a description of how the teacher percibes his professional ethic and how this relates with his labour performance. This issue is trascendental as we are in a time in which it is said the values have been lost. For instance, we are looking foward to propiciate that these can be retaken at the classroom so the students, when they graduate, are comitted people not only with their professional tasks but also with their environment: their community, country and the planet itself and in this aspect, the ethic and the professional tasks of the teacher are fundamental. In the development of the current investigation, the Inventory of Teacher’s Ethical Behaviour of Ana Hirsch Adler and the Inventory of Labour Performance of Manuel Torres were used. The statistical analyses the tests were submitted to indicate us that the instruments are valid and reliable. These tests were taken to 304 teachers of a district of Lima. The statistical results indicate us that the professional ethic is significantly related to labour performance of the teachers. Moreover, it was found that signifcant differences exist between the teachers of the educative instutions of the sample regarding the variables in study.